Motor control and cerebral hemispheric specialization in highly qualified judo wrestlers - Mikheev, M.; Mohr, C.; Afanasiev, S.; Landis, T.; Thut, G. (Neuropsychologia, 2002)
With the purpose of investigating motor and cognitive lateralization profiles associated with long-term motor training, we investigated differences in hemispheric specialization between proficient judo sportsmen and controls through the assessment of a number of handedness and footedness items including postural preferences as well as dichotic listening and lateralized visual field tests. Our data show that: (1) the different handedness and footedness items did differently relate to each other within the athlete and control groups as revealed by a principle component analysis (PCA); (2) stand side correlated differently to these motor profile factors in athletes and controls; (3) athletes preferred more frequently to perform certain movements with the left hand than controls, although overall right-handed; (4) this was especially true for athletes which proved to be most proficient/skilled; and (5) in a lateralized verbal listening task and a lateralized visual field task athletes revealed enhanced right-hemispheric involvement relative to controls. Our results suggest that during motor and postural skill acquisitions (long-term judo training) lateral preferences are modified, probably due to neuroplasticity. Moreover, the present findings support the multidimensional view of handedness by Steenhuis and Bryden [Cortex 25 (1989) 289] and the notion of a right-hemispheric "praxis system" involved in skilled action routines within peripersonal space [Brain and Cognition 23 (1993) 181].